Analisis Yuridis Penerapan Pasal Kekerasan Seksual pada Kasus Pelecehan Anak di Bawah Umur - Molly, Guldoninthon J. (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
This study aims to examine legally how judges' decisions consider the elements of criminal acts of sexual violence against children, as well as their legal implications in the context of child protection. The focus of this research includes an analysis of the disparity between positive law and social reality, as well as the importance of integrated rehabilitation and institutional restoration to realize a holistic protection system. This study uses a juridical-normative method with a case study approach. Data were collected through document analysis, such as court decisions, laws and regulations (including Law No. 35 of 2014 concerning Child Protection and the Criminal Procedure Code), legal journals, and related literature. This approach also involves an analysis of legal interpretations, such as grammatical and systematic interpretations, to understand the meaning and interrelationships between legal provisions and to evaluate the effectiveness of criminal sanctions in creating a deterrent effect. The results of the study indicate a significant gap between legal formulation and implementation in the field. The lack of specific regulations, particularly regarding the ever-evolving modus operandi of sexual violence, as well as procedural and substantive obstacles in the implementation of restitution and rehabilitation for victims are major obstacles. Although the legal framework has attempted to protect children, challenges remain in law enforcement and inter-institutional coordination. Adaptive regulatory reforms, increased law enforcement capacity, and a multi-sectoral approach that integrates preventive and curative efforts are needed. In conclusion, criminal justice system reform is needed to integrate a restorative justice approach that focuses on victim and community recovery.